COMMUNITY EMPOWERMENT THROUGH ENTREPRENEURSHIP DEVELOPMENT OF PROCESSED HARUAN FISH FOR HOUSEWIVES IN TUMBANG RUNGAN VILLAGE PALANGKA RAYA CITY - Yesninopy; Saifulloh Darlan; Wahidin; Kusnida Indrajaya; Hendrowanto Nibel; Susan Daniel; Endah Yusma Pratiwi; Ade Yusuf Ferudyn; Mardiana; Dinda (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2023)
The objectives of community empowerment can be formulated as follows: 1). Providing Skills Training on processing Haruan Fish into Prozenfood Products (Nuggets, Dim Sum, and Pentol) Haruan Fish for housewives in Tumbang Rungan Village. 2) Providing Information about the Benefits Haruan Fish for Health for mothers in Tumbang Rungan Village. The community empowerment implementation methods used are lectures, demonstrations, practice, and questions and answers which are used to provide skills training in processing Haruan fish into Nuget, Dim Sum and Pentol products as well as providing information about the benefits of Haruan fish for health. The results of Community Empowerment through fostering entrepreneurship in processing Haruan fish for housewives in the Tumbang Rungan sub-district, Palangkaraya City are mothers who gain new knowledge and skills related to the use of Haruan fish (previously, during the dry season the fish was abundant, the fish were only sold, made into salted fish, and discarded as fish food). Get information about the nutrition of Haruan fish for children's health in dealing with stunting. The hope is to help marketers, for example in bazaar activities, WhatsApp and Instagram promotions, as well as making permits for processed Haruan fish products.